2018
DOI: 10.1002/cche.10081
|View full text |Cite
|
Sign up to set email alerts
|

Insight of aroma in brown rice through chemical assessment of 2‐Acetyl‐1‐pyrroline (2AP) in aromatic germplasm of India

Abstract: Background and objectives Fragrance and flavor of aromatic rice are chief indicators for consumer acceptability. Aroma is evaluated by time‐consuming and labor‐intensive sensory or chemical methods. In this study, we aimed volatile profiles of aromatic rice germplasm. Findings Considering the volatile nature of aroma compounds, highly sensitive and robust gas chromatography mass spectrometry (GC‐MS) analysis is the best alternative and can accurately assess the volatile aromatic compounds. Aromatic (552) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Applying an improved headspace solid-phase micro-extraction (HS-SPME) method combined with a GC-MS assay to a collection of 228 aromatic rice germplasm, the 2AP content in 34 genotypes was reported to be below the limit of detection (Xie et al 2019). In addition to 2AP, six volatile compounds like nonanal, hexanal, hydroxyl methyl furfural, indole, benzyl alcohol, and guaiacol were detected at similar concentration in the aromatic germplasm (Peddamma et al 2018). This suggested that it is premature to identify one or more of these compounds as responsible for the desired aroma considering the specificity of olfactory receptors and their highly varying odor detection threshold for individual compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Applying an improved headspace solid-phase micro-extraction (HS-SPME) method combined with a GC-MS assay to a collection of 228 aromatic rice germplasm, the 2AP content in 34 genotypes was reported to be below the limit of detection (Xie et al 2019). In addition to 2AP, six volatile compounds like nonanal, hexanal, hydroxyl methyl furfural, indole, benzyl alcohol, and guaiacol were detected at similar concentration in the aromatic germplasm (Peddamma et al 2018). This suggested that it is premature to identify one or more of these compounds as responsible for the desired aroma considering the specificity of olfactory receptors and their highly varying odor detection threshold for individual compounds.…”
Section: Discussionmentioning
confidence: 99%